2021
DOI: 10.7759/cureus.16940
|View full text |Cite
|
Sign up to set email alerts
|

The Spectrum of Hemolytic Disease of the Newborn: Evaluating the Etiology of Unconjugated Hyperbilirubinemia Among Neonates Pertinent to Immunohematological Workup

Abstract: Background and objectiveThe exact burden of hemolytic disease of the newborn (HDN) attributed to neonatal unconjugated hyperbilirubinemia (NUH) in developing nations is still unclear. Still, anti-D is reported to be the most common cause of HDN in India. ABO incompatibility has emerged as a leading cause of exchange transfusion (ET) in many countries. But many centers in our country rely on direct antiglobulin test (DAT) as a screening tool to evaluate immunological causes, whereas advanced immunohematological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 27 publications
2
6
0
1
Order By: Relevance
“…Because of the Rh D antigen, HDFN was still existing, as the study showed. Nevertheless, prophylaxis IgG (D) immunoglobulin was utilized; our results are concordant with several previous studies (Bi et al, 2019;Erickson, 2020;Routray et al, 2021). which may indicate improperly or shortage of immunoglobulin dose.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Because of the Rh D antigen, HDFN was still existing, as the study showed. Nevertheless, prophylaxis IgG (D) immunoglobulin was utilized; our results are concordant with several previous studies (Bi et al, 2019;Erickson, 2020;Routray et al, 2021). which may indicate improperly or shortage of immunoglobulin dose.…”
Section: Resultssupporting
confidence: 92%
“…A diagnosis of ABO HDFN was made in (16.4%), in the current analysis; Bhat YR and Kumar CG, in 2012 (17.3%), agreed with this frequency to the Indian study (Routray et al, 2021) but when Feng CS, Wan CP, et al, who was from Hong Kong, found the incidence of ABO HDFN was 20% among infants with a serum bilirubin level of 300 mmols/L or more, it slightly reduced than frequency (Bi et al, 2019), and our results were slightly lower than this. It may be because their serum bilirubin concentration criteria was short.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…More sensitive tests like heat elution or the Lui's freeze technique can help in negative DAT for better diagnosis of ABO HDN. 9…”
Section: Discussionmentioning
confidence: 99%
“…Among Asian populations, in India there is a high correlation between the rates of prenatal ABO incompatibility and postnatal ABO-HDN incidence. In Singapore, the correlation between prenatal ABO incompatibility rates and postnatal ABO-HDN occurrence is low, and in China ABO incompatibility accounts for 20-25% of mothers and infants (4). Data on the incidence Original Article Application of IgG antibody titer and subtype in diagnosis and severity assessment of hemolytic disease of the newborn of postnatal ABO-HDN also vary, which is believed to account for the 10-20% of ABO incompatibility between mothers and infants, while the incidence of ABO-HDN is reported to be between 2% and 5% (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%